(untitled) (International Journal of Engineering and Computer Science, 2017)
Digital watermarking enables one to protect the document; it is the kind of material authentication. The major problem in hypermedia technology is attacks on digital watermarking.In digital watermarking single attack on a given watermark image has effective outcome but multiple attacks on a given watermarked image and other watermark scrambling need to be improved. This paper purposes a new watermarking technique using integrated approach of SWT with GA and PSO for watermarking scrambling is used. The proposed methodology enhances imperceptibility and robustness in the watermarked image which has result in improving the visual quality of watermark.